POTENTIAL OF ASHITABA LEAF FLOUR Angelica keiskei AS A PHYSIOTHOTIC SOURCE IN FEED ON PHYSICAL QUALITY OF MALE QUAIL MEAT (Coturnix coturnix japonica) FINAL PHASE (FINISHER) - Dina Oktaviana; Supriadi; Maratun Jannah (JURNAL SANGKAREANG MATARAM, 2020)
Physical quality of good quail meat requires feed that has good quality and quantity. One source or feed material that can be used as a source of phytobiotics is Ashitaba leaf. As a source of phytobiotics Ashitaba (Angelica keiskei) is a multi-functional plant because it is rich of vitamins, minerals, amino acids, mineral elements and many active substances. The purpose of this study was to determine the physical quality of final phase (finisher) male quail (Coturnix coturnix japonica) meat which are given additional feed ingredients in its ration in the form of Ashitaba Angelica keskei leaf flour. This study used 5 different types of feed treatments with 4 replications so that 20 male quails were distributed in 20 cage unit experiments. Five kinds of treatment were P0 = 98% basal feed, 2% filler, 0% Ashitaba leaf flour, P1 = 98% basal feed, 1.5% filler, 0.5% Ashitaba leaf flour, P2 = 98% basal feed, 1 % filler, 1% Ashitaba leaf flour, P3 = 98% basal feed, 0.5% filler, 1.5% Ashitaba leaf flour, P4 = 98% basal feed, 0% filler, 2% Ashitaba leaf flour, parameters in quality physical meat includes pH testing, water holding capacity and cooking losses. All data obtained were statistically analyzed with a complete randomized design test in the same direction and variance of the Annova via SPSS and if there were differences further tested by Duncan's test. Based on statistical analysis shows that the pH value, water holding capacity and cooking losses are not significantly different or non-significant meaning, giving Ashitaba leaf flour in male quail feed up to 2% level has not significantly affected the physical quality of meat.